Obstacles to Sustainable Development Programs in Libyan Society (Journal of human and social sciences, 2023)
Sustainable development is a key issue that plays a significant role in improving quality of life in various aspects—particularly the social dimension—and especially in developing countries that continue to struggle with underdevelopment. In Libya, sustainable development programs have faced multiple obstacles that hindered their success at both the social-environment level and the planning level, despite the availability of vast oil resources. The study reviews the concepts of sustainable development, planning, and social development, analyzes the main stages of Libya’s development efforts, and highlights the economic, cultural, and social challenges that impeded progress. It concludes that achieving sustainable development in Libya requires strategies tailored to the local context, a supportive socio-economic environment, and the adoption of systematic planning and institutional coordination to ensure successful projects and genuine socio-economic transformation. Keywords: Sustainable Development Programs – Planning – Social Development.
Keywords: Development Constraints; Sustainable Development; Libyan Society; Administrative Corruption; Oil Dependency